2015
DOI: 10.1073/pnas.1511238112
|View full text |Cite
|
Sign up to set email alerts
|

Plant Raf-like kinase integrates abscisic acid and hyperosmotic stress signaling upstream of SNF1-related protein kinase2

Abstract: Plant response to drought and hyperosmosis is mediated by the phytohormone abscisic acid (ABA), a sesquiterpene compound widely distributed in various embryophyte groups. Exogenous ABA as well as hyperosmosis activates the sucrose nonfermenting 1 (SNF1)-related protein kinase2 (SnRK2), which plays a central role in cellular responses against drought and dehydration, although the details of the activation mechanism are not understood. Analysis of a mutant of the moss Physcomitrella patens with reduced ABA sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 51 publications
10
147
1
5
Order By: Relevance
“…These results indicate that SnRK2a, but not MPKs, functions in a canonical ABA signaling pathway in P. patens. Saruhashi et al (2015) recently reported similar findings of SnRK2 and not MPK activity induced in (A) Evans blue staining 2 d after spraying with water (white bars) or 2 3 10 5 B. cinerea spores per milliliter (gray). Staining measured as OD 600 per mg dry weight (DW).…”
Section: Discussionsupporting
confidence: 66%
“…These results indicate that SnRK2a, but not MPKs, functions in a canonical ABA signaling pathway in P. patens. Saruhashi et al (2015) recently reported similar findings of SnRK2 and not MPK activity induced in (A) Evans blue staining 2 d after spraying with water (white bars) or 2 3 10 5 B. cinerea spores per milliliter (gray). Staining measured as OD 600 per mg dry weight (DW).…”
Section: Discussionsupporting
confidence: 66%
“…For example, BRASSINOSTEROID INSENSITIVE2 was found to positively modulate ABA signaling through phosphorylation of subgroup III SnRKs in Arabidopsis (Cai et al, 2014), and ARK plays an essential role in the activation of SnRK2 in the moss Physcomitrella patens (Cai et al, 2014;Saruhashi et al, 2015). Recently, ABI1 was found to be degraded through ubiquitination by PUB12 and PUB13 in the presence of ABA and an ABA receptor in Arabidopsis, which may be regarded, to our knowledge, as a new positive regulation pathway of ABA signaling (Kong et al, 2015).…”
Section: Osbzip23 Positively Regulates the Aba Level In Ricementioning
confidence: 92%
“…Because osmotic stress triggers a cytosolic calcium signal and because the calcium channel OSCA1 is a putative osmosensor (Yuan et al, 2014), candidate factors upstream of the SnRK2s include calcium-responsive kinases such as CPKs and SCaBP/CBL-PKS/CIPKs (Figure 3). In the moss Physcomitrella patens , recent work showed that a Raf-like kinase is critical for SnRK2 activation by both osmotic stress and ABA (Saruhashi et al, 2015). It will be of interest to determine whether and how similar kinases may integrate osmotic stress and ABA signaling in higher plants.…”
Section: Osmotic Stress Signalingmentioning
confidence: 99%